Study of the load during official competition in professional women`s basketball - A case study - López-Sierra, P.; Jiménez-Sáiz, S. L.; García-Rubio, J.; Piñar, M. I.; Ibáñez, S. J. (Sports, 2025)
Background: Basketball matches involve numerous conditioning factors which, when put together, make for a complex prediction event. However, unraveling all these elements in different studies allows the control of certain conditioning factors of the game, giving rise to more stable and controlled games. Objectives: Due to the absence of studies that analyze professional matches in women`s basketball, the aim of the present research is to analyze the influence of the result, partial result and specific positions on the load in official competition between two women`s teams that play a match simultaneously.